Estimation of the water productivity of different varieties of wheat and rice in the context of agronomic, physiological and nutritional attributes - Abbas, Moneeza; Nawaz, Sadia; Fatima, Ammara; Kamran, Muhammad; Aslam, Fakhra; Atif, Saima; Younas, Fatima (International Journal of Agricultural and Biological Engineering, 2024)
Water shortage is a global concern, it also poses a particularly severe threat in Pakistan. It is estimated that over 60% of this irrigation water is not efficiently applied or not efficiently utilized by crop depending upon genetic variability. The pot study was conducted to evaluate the water efficiency of various wheat varieties (Millat 2011, Galaxy 2013, Faisalabad 2008, and Gandum 1) and rice varieties (Punjab Basmati, Chenab Basmati, B-515, and PS-2) based on their photosynthetic efficiency and nutritional quality by measuring their protein and chlorophyll contents. The highest concentrations of protein and chlorophyll were observed in plants of both crops that were watered and cultivated with 50 mL of water. For wheat, the greatest leaf length (cm), net assimilation rate [g/(d∙m2)], and photosynthetic efficiency were achieved when 80 mL of water was applied. Similarly, rice varieties (Punjab Basmati, Chenab Basmati, B-515, and PS-2) exhibited the highest photosynthetic efficiency, leaf length, net assimilation rate, and chlorophyll content when grown with 80 mL of water. Therefore, a conservative cultivation of wheat and rice is possible by selecting efficient variety and by improving technological approach of water saving through irrigation level and wise scheduling. The judicious use of water not only limit losses but also improve the the losses and improving productivity particularly in scenario of water scarcity. Keywords: water productiviy, wheat; rice, agronomy, physiology, nutritionDOI: 10.25165/j.ijabe.20241705.7514Citation: Abbas M, Nawaz S, Fatima A, Kamran M, Aslam F, Atif S, et al. Estimation of the water productivity of different varieties of wheat and rice in the context of agronomic, physiological and nutritional attributes. Int J Agric & Biol Eng, 2024; 17(5): 200-205.